99mTc-sodium phytate is a valid alternative to the gold-standard 99mTc-sulfur colloid in the measurement of gastric emptying among healthy multi-ethnic Asian population: results of a randomized cross-over trial - Norazlina Mat Nawi; Nashrulhaq Tagiling; Mohd Fazrin Mohd Rohani; Wan Mohd Nazlee Wan Zainon; Muhammad Saifuddin Zanial; Mung Seong Wong; Yeong Yeh Lee (BMC Gastroenterology, 2020)
Abstract Background It is unclear if the 99mTc-sodium phytate (99mTc-SP) is as reliable as the gold-standard 99mTc-sulfur colloid (99mTc-SC) for gastric emptying scintigraphy (GES). This study is aimed to compare the emptying rates of both radiotracers in a prospective, randomized cross-over trial and to determine the normative data of a healthy multi-ethnic Asian population. Methods Out of the 44 healthy individuals screened, 31 (14 females; mean age: 28.4 ± 7.0 years) were enrolled and underwent GES using the standardized egg-white meal. All participants were randomly assigned to either 99mTc-SP or 99mTc-SC on the first GES session before crossed over to the other formulation after 2 weeks. Results Both kits achieved the radiochemical purities of > 95%. The median rate (95th upper normative limit) of gastric emptying, reported as total gastric meal retention between 99mTc-SP and 99mTc-SC, was found to be comparable at all measured time points: 0.5 h [85.0% (96.6%) vs. 82.0% (94.0%)], 1 h [70.0% (86.4%) vs. 65.0% (86.6%)], 2 h [31.0% (55.8%) vs. 25.0% (64.4%)], 3 h [7.0% (26.3%) vs. 5.0% (29.9%)], and 4 h [3.0% (10.3%) vs. 2.0% (9.9%)]; P > 0.05. In addition, both radiotracers correlated well (Kendall’s Tau (τ) coefficient = 0.498, P < 0.001) and presented with a good agreement at the 4th-hour time frame based on the Bland-Altman plot analysis. Conclusions 99mTc-SP is a valid radiotracer alternative to 99mTc-SC for routine GES examination. The normative values for both radiotracers have also been determined for the healthy multi-ethnic Asian population. Trial registration This trial was registered retrospectively in the Thai Clinical Trials Registry on May 23rd, 2020 (Identifier: TCTR20200526004; http://www.clinicaltrials.in.th/index.php?tp=regtrials&menu=trialsearch&smenu=fulltext&task=search&task2=view1&id=6296 ).